PENGARUH MEDIA AUDIO VISUAL TERHADAP HASIL BELAJAR IPA PESERTA DIDIK DI SEKOLAH DASAR MUJAHIDIN - Nugraha Lubis, Ade Apriliadi; Rosnita, Rosnita; Marli, Suhardi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThe problem in this study is whether there is an impact and how much the influence of the use of audio visual media on learning natural knowledge of the learning outcomes of participants in class III elementary school of the South Pontianak Mujahidin. This study aims to analyze whether there is an influence and how much influence the audio visual media on learning Natural Sciences on learning outcomes. This study used an experimental method with Pre-Experimental Design type of non equivalent control group design. The population is all students from five classes totaling 166 people, the sample is all students totaling 68 people. Data collection techniques are measurements, with a data collection tool is an objective written test. Based on the data analysis, the results of the average post-test experimental class = 79.32 and the average post-test results of the control class = 66.73. This shows an increase in learning outcomes of students in learning using audio visual media. After t test obtained tcount 6.88 for dk 62 and ? = 5% obtained t table = 1.6705, which means that t count ? t table, then Ha is accepted, which means there is a significant impact on the use of audio visual media. From the calculation of the effect size (? ?), obtained ? ? is 1.24 with high criteria. Means the use of audio visual media in learning Natural Sciences gives a high influence on the learning outcomes of students. Keywords: Audiovisual Media, Learning Outcomes, Natural Science Education.